Development and Validation of Organizational Socialization Scale - Erdoğan, Ufuk; Donmez, Burhanettin (My University, 2019)
The purpose of this study is to develop a valid and reliable scale for determiningteachers' organizational socialization levels. The study group consists of 814 teachersworking in primary and secondary schools in Malatya. In the items' developmentprocess, firstly the literature review was carried out and the scale items were preparedbased on the literature review. Then, exploratory and confirmatory factor analyseswere conducted to evaluate the construct validity of the scale. The internal consistencyof the scale was assessed by calculating Cronbach's ? for each subscale. Exploratoryfactor analysis revealed that 24 items loaded on five factors, with factor loadings thatranged from .46 to .84. Confirmatory analysis results clearly indicated that the fivefactor model was a good fit for the data. The results showed that Cronbach’s ?coefficients ranged from .84 to .91, indicating high internal consistency. The findingsobtained as a result of the validity and reliability studies suggest that the scaledeveloped can be used as a valid and reliable instrument in determining teachers'organizational socialization levels.
Keywords: Eğitim; Eğitim Araştırmaları